Best practices for US Department of Defense model validation: lessons learned from irregular warfare models. (October 2013) - Appleget, Jeffrey; Blais, Curtis; Jaye, Michael
The US Department of Defense (DoD) requires all models and simulations that it manages, develops, and/or uses to be verified, validated, and accredited. Critical to irregular warfare (IW) modeling are interactions between combatants and the indigenous population. Representation of these interactions (human behavior representation (HBR)) requires expertise from several of the many fields of social science. As such, the verification, validation, and accreditation (VVA) of these representations will require adaptation and, in some cases, enhancement of traditional DoD VVA techniques. This paper suggests validation best practices for the DoD modeling community to address new challenges of modeling IW.